Highly sensitive hydrogen analysis employing low pressure laser induced breakdown spectroscopy in helium surrounding gas under electric field - Indra Karnadi; Marincan Pardede; Rinda Hedwig; Ivan Tanra; Maria Margaretha Suliyanti; Marvin Yonathan Hadiyanto; Eric Jobiliong; Ihan Martoyo; Zener Sukra Lie; Kiichiro Kagawa; Tjung Jie Lie; Koo Hendrik Kurniawan (Scientific Reports)
Abstract We conduct an experimental study to search for the urgently needed method for routine, no sample pretreatment, in-situ, and less-destructive analysis of Hydrogen (H) content in Zircaloy-4 tube used as radioactive fuel container in light water nuclear power plant. For this purpose, we implemented laser-induced breakdown spectroscopy (LIBS) in Helium (He) surrounding gas at a relatively low pressure of around 3 kPa and low laser energy of 17 mJ. In addition, we designed a new compact and portable sample chamber accommodating an open end so the chamber can tightly fit the Zircaloy-4 tube surface. Inside the chamber we put electrodes to apply an additional electric field. We found that applying an electric field in the plasma expansion region increases the H emission intensity by a factor of 6. Consequently, the H I 656.2 nm emission line obtained from the Zircaloy-4 sample containing H of 11 ppm impurity featuring a sharp linewidth (0.1 nm) with high signal-to-noise ratio (S/N = 120). Thus, it offers potential applications to non-destructive H analysis in Zircaloy-4 tubes used in light water nuclear power plant. The detection limit of H was estimated less than 0.26 ppm, well below the sensitivity limit of around 600 ppm required for the regular inspection of Zircaloy-4 tubes in light water nuclear power plant.